Descriptive epidemiology of sports injury and illness during the Rio 2016 Olympic Games: A prospective cohort study for Korean team - Yoon, J.; Bae, M.; Kang, H.; Kim, T. (International Journal of Sports Science & Coaching, 2018)
This study aimed to analyze the characteristics of injuries and illnesses that occurred during the Rio 2016 Olympic Games for Korean team by using a prospective cohort design. In total, 204 Korean athletes competed in 24 sporting events during the Olympic Games. The entire medical staff of the Korean team recorded injuries and illnesses on a daily basis that occurred during training and competition using the International Olympic Committee injury and illness surveillance system. During the Olympic Games, 308 injuries and 73 illnesses were reported; the incidence was 150.9 injuries and 35.8 illnesses per 100 athletes. In addition, 56.3% and 24.0% of all athletes sustained at least one injury or illness, respectively. The highest rate of injuries was observed in boxing and wrestling, whereas the highest rate of illnesses was seen in boxing and swimming. Twelve percent of all injuries resulted in absenteeism from training or competition for at least 1 day. Of all infections, 75.9% occurred in the respiratory tract. In addition, 2.7% of all illnesses prevented athletes performing their sport for 1 day. These results may be used to further analyze mechanisms of injury and their risk factors in Olympic sports to develop effective preventive strategies for athletes.